SECONDARY TEACHERS' PERCEPTIONS TOWARDS TEAM TECHING IN TEACHING SCIENCE IN ENGLISH : A CASE STUDY - Fauziah Rina, Verador (Universiti Malaysia Sarawak, (UNIMAS), 2008)
This paper aims to find out secondary teachers' perceptions towards team teaching in teaching Science in English. Data gathered among eight secondary teachers' using semistructured interview in Kota Kinabalu District. Results suggest that teachers' perceptions towards team teaching in teaching Science in English are more to positive needs because of the benefits it serves. Most of teachers are interested in team teaching as well as the students because they can increase in term of language proficiency and personal development of the subject matter. This outcome may provide new insights for those teachers who want to try out this technique to the schools.